COMMENTS TO JOEL ROBBINS ARTICLE “RELIGIOUS PLURALISM AND VALUE PLURALISM: RITUAL AND THE MANAGEMENT OF INTERCULTURAL DIVERSITY” - Sarro, Ramon (Debates do NER, 2014)
COMMENTS TO JOEL ROBBINS ARTICLE “RELIGIOUS PLURALISM AND VALUE PLURALISM: RITUAL AND THE MANAGEMENT OF INTERCULTURAL DIVERSITY”